Respuesta :

Hope this helps ya! :)
Ver imagen Sara885

Answer:

Step-by-step explanation:

1. (2x- 1)(x + 7) =                                     (x - 7)(x + 3)

  2x^2 + 14x - x - 7 =                            x^2 + 3x - 7x - 21 =

  2x^2 + 13x - 7 =                                  x^2 - 4x - 21 =

  2x^2 + 13x = 7                                     x^2 - 4x = 21

2. 6x^5 + 15x^2 =                                8x^4 - 6x =

   3x^2(2x^3 + 5)                                2x(4x^3 - 3)

3. 6x^2 + 15x + 9 =                           14x^2 - 18x + 4 =

   3(2x^2 + 5x + 3) =                         2(7x^2 - 9x + 2) =

   3(2x + 3)(x + 1)                                2(7x - 2)(x - 1)

4. 3x^2 + 2x - 1 =                                x^2 + 10x + 16 =

  (3x - 1)(x + 1)                                     (x +2)(x + 8)